Epistemologi Ekonomi Islam dan Pengembangannya pada Kurikulum Ekonomi Islam di Perguruan Tinggi - Rozalinda, Rozalinda (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2015)
Islamic economics as a discipline has a foundation of epistemology. The main problem in the development of economics and Islamic finance in Indonesia is still the gap between the needs of industry and graduate from college. This study aims to analyze how epistemology and the development of Islamic economics and the curriculum structure of Islamic economics in universities that teach Islamic economics and what is effective approach to be applied so that graduates can meet the needs of the financial industry Islamic economics. The method used in this study is a content analysis is used to explain the depth of the curriculum of Islamic economics in college. Based on the results of the study found that the difference was the presence of Islamic economics learning systems in higher education so that graduates produced by universities that teach Islamic economic is still little that can meet the market needs of the Islamic financial industry.